2015
DOI: 10.1186/s12978-015-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Official invitation letters to promote male partner attendance and couple voluntary HIV counselling and testing in antenatal care: an implementation study in Mbeya Region, Tanzania

Abstract: BackgroundThe benefits of male partner involvement in antenatal care (ANC) and prevention of mother-to-child transmission of HIV (PMTCT) for maternal and infant health outcomes have been well recognised. However, in many sub-Saharan African settings, male involvement in these services remains low. Previous research has suggested written invitation letters as a way to promote male partner involvement.MethodsIn this implementation study conducted at three study sites in southwest Tanzania, acceptability of writt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
7
42
0
1
Order By: Relevance
“…Furthermore, the HOPE intervention reached more men than other interventions reported in the literature, including invitation plus phone and in-person tracing of male partners to come to the clinic for testing (52% of men), 28 home-based door-to-door testing (only 28% of those met in the home were men, and 75% of household members were tested), 32 and written invitations alone without follow-up (up to 54% effectiveness). 26 However, a one-size-fits-all approach may not be as efficient as leveraging multiple strategies, which would be reasonable given that invitations and partner tracing to come to clinic have recently demonstrated reaching a relatively high proportion of men in the studies by Osoti et al 27 and Rosenberg et al 28 published in 2015. Each of these methods could be included as part of an escalating strategy of male partner involvement during the antenatal period, starting with invitations then phone tracing to attend clinic, and scheduled home-based visits for those who are not reached with the first methods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the HOPE intervention reached more men than other interventions reported in the literature, including invitation plus phone and in-person tracing of male partners to come to the clinic for testing (52% of men), 28 home-based door-to-door testing (only 28% of those met in the home were men, and 75% of household members were tested), 32 and written invitations alone without follow-up (up to 54% effectiveness). 26 However, a one-size-fits-all approach may not be as efficient as leveraging multiple strategies, which would be reasonable given that invitations and partner tracing to come to clinic have recently demonstrated reaching a relatively high proportion of men in the studies by Osoti et al 27 and Rosenberg et al 28 published in 2015. Each of these methods could be included as part of an escalating strategy of male partner involvement during the antenatal period, starting with invitations then phone tracing to attend clinic, and scheduled home-based visits for those who are not reached with the first methods.…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, HIV-infected pregnant women who reported that their partner had been tested for HIV had lower rates of vertical transmission and infant mortality, but awareness of partner HIV status was not captured [36]. Current interventions to improve PMTCT partner testing include mailed invitations and home-based HIV testing procedures [3741]. Although our study did not capture disclosure information, HIV status disclosure during pregnancy (to anyone, but particularly to the male partner) has been associated with ARV use in PMTCT [15, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Fraction of husbands of married pregnant women who get tested if given invitation letters 0.33 0.15-0.53 [74][75][76][77][78] OR for effect of marriage on probability of pregnant women's partner getting tested 4.00 - 76,79,80 OR for effect of self-testing offer on uptake of testing 8.17 6.33-10.24 16 Probability of starting ART soon after diagnosis Table 1. HIV testing assumptions.…”
Section: Methodsmentioning
confidence: 99%